Clinical InvestigationsOriginal articleInterstitial brachytherapy for penile cancer: the experience of Oncology Centre in Bydgoszcz - Makarewicz, Roman; Lebioda, Andrzej; Terlikiewicz, Joanna; Kabacińska, Renata (Journal of Contemporary Brachytherapy, 2010)
Purpose : The aim of this work was to analyze the treatment results and complications of patients with penile cancer treated in our centre. Material and methods : Thirty three patients were included in this retrospective research. The average age was 62. All patients underwent brachytherapy HDR or PDR procedures using a remote-after-loading system with iridium source. Results : Average follow-up was 60 months. Complete remission was observed in 24 patients (72.7%) out of the whole group. Locoregional and distant recurrences were noted in 9 patients (27.3%). In all patients 5-year overall and disease free survival were 84.9% and 75.4%, respectively. The 5-year locoregional control rate was 78.8%. Conclusion : Radical brachytherapy could possibly be a good treatment option in selected patients with T1-3 penile cancer and lesions smaller than 4 cm in diameter.